1993
DOI: 10.1111/j.1526-100x.1993.tb00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Removal from Natural Waters Using Controlled Algal Production

Abstract: A series of experiments designed to demonstrate the potential of using managed, attached algal production to permanently remove excess phosphorus from agricultural run‐off is described. The experiments were carried out on a secondary canal in the New Hope South region of the Florida Everglades Agricultural Area from October, 1991, to May, 1992. Natural algal populations of periphyton, including species of the genera Cladophora, Spirogyra, Enteromorpha, Stigeoclonium, and a variety of filamentous diatoms such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
2
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(74 citation statements)
references
References 7 publications
1
68
2
3
Order By: Relevance
“…Using hand and vacuum harvesting of the periphyton, they achieved P removal rates ranging from 104 to 139 mg TP·m Ϫ2 ·d Ϫ1 . Nutrient removal rates were lower in our study compared to removal rates found by Adey et al (1993). In Experiment 1 the presence of the fish resulted in an increase in movement of P and N from the water to the sediment sink, and significant masses of P were also incorporated into their tissue as the fish grew.…”
Section: Discussioncontrasting
confidence: 48%
See 3 more Smart Citations
“…Using hand and vacuum harvesting of the periphyton, they achieved P removal rates ranging from 104 to 139 mg TP·m Ϫ2 ·d Ϫ1 . Nutrient removal rates were lower in our study compared to removal rates found by Adey et al (1993). In Experiment 1 the presence of the fish resulted in an increase in movement of P and N from the water to the sediment sink, and significant masses of P were also incorporated into their tissue as the fish grew.…”
Section: Discussioncontrasting
confidence: 48%
“…Vymazal (1988) found that a trough system containing screens with periphyton removed both P and N. Adey et al (1993) examined nutrient removal from agricultural runoff by natural algal populations in raceways. Using hand and vacuum harvesting of the periphyton, they achieved P removal rates ranging from 104 to 139 mg TP·m Ϫ2 ·d Ϫ1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Small-scale algal growth chambers are used in aquaria, in a variety of mesocosms, and for the commercial production of coral reef organisms (Adey and Loveland, 1998). Large-scale ATS units are in commercial use for treating wastewater generated by tilapia aquaculture operations (Adey and Loveland, 1998), agricultural runoff (Adey et al, 1993), and for N and P removal in tertiary treatment of municipal wastewater (Craggs et al, 1996a,b).…”
Section: Introductionmentioning
confidence: 99%